An ANOCEF Genomic and Transcriptomic Microarray Study of the Response to Irinotecan and Bevacizumab in Recurrent Glioblastomas. (2nd April 2014) - Laffaire, Julien; Stefano, Anna Luisa Di; Chinot, Olivier; Idbaih, Ahmed; Gallego Perez-Larraya, Jaime; Marie, Yannick; Vintonenko, Nadia; Boisselier, Blandine; Farina, Patrizia; Delattre, Jean-Yves; Figarella-Branger, Dominique; Honnorat, Jérôme; et al.
Abstract : Background . We performed a retrospective study to assess whether the initial molecular characteristics of glioblastomas (GBMs) were associated with the response to the bevacizumab/irinotecan chemotherapy regimen given at recurrence. Results . Comparison of the genomic and gene expression profiles of the responders (n = 12 ) and nonresponders (n = 13 ) demonstrated only slight differences and could not identify any robust biomarkers associated with the response. In contrast, a significant association was observed between GBMs molecular subtypes and response rates. GBMs assigned to molecular subtype IGS-18 and to classical subtype had a lower response rate than those assigned to other subtypes. In an independent series of 33 patients, neither EGFR amplification nor CDKN2A deletion (which are frequent in IGS-18 and classical GBMs) was significantly associated with the response rate, suggesting that these two alterations are unlikely to explain the lower response rate of these GBMs molecular subtypes. Conclusion . Despite its limited sample size, the present study suggests that comparing the initial molecular profiles of responders and nonresponders might not be an effective strategy to identify biomarkers of the response to bevacizumab given at recurrence. Yet it suggests that the response rate might differ among GBMs molecular subtypes.